Ice in the Outback: the epidemiology of amphetamine-type stimulant-related hospital admissions and presentations to the emergency department in Hedland, Western Australia. (August 2018) - Monahan, Caitriona; Coleman, Mathew
Objectives: Despite research showing higher use of amphetamine-type stimulants (ATS) in rural areas, limited research has examined the epidemiology of ATS-related presentations and admissions to remote regional centres. To determine the epidemiology of ATS-related (a) Emergency Department (ED) presentations and (b) inpatient admissions over a five-year period at the Hedland Health Campus (HHC) in remote Western Australia. Methods: A retrospective review of medical records was conducted. Demographic data including gender, age and indigenous status were captured. Results: Four hundred and eighty-two ATS-related hospital presentations were identified during the study period. The most common reason for ED presentation was mental and behavioural problems. Of those presenting, 66% were male and 69% identified as Aboriginal. ATS-related ED presentations increased seven-fold over the study period. Ninety-nine ATS-related inpatient admissions were identified during the study period. Psychotic disorder was the most common reason for admission. Males made up 75% of admissions and 53% identified as Aboriginal. Conclusions: This study showed a disproportionally high burden of ATS-related harm among Aboriginal people. The number of ATS-related ED presentations and inpatient admissions increased significantly over the study period.